O princípio da confusão na comunicação. - DRAVET, Florence Marie; DE CASTRO E SILVA, Gustavo; ALVES, Paulo César (Chasqui (13901079), 2019)
From the analysis of the myths related to Exu in Afro-Brazilian culture, we will explore the notion of confusion in communication, beyond those of information noise and fake news, but associated with a principle of immanence of language and language. Our methodology is that of the mythological interpretation in the light of Afro-Brazilian ethnographic and bibliographic knowledge. We conclude that in the myths of Exu, if confusion is principle, it does not happen without a demand for organization.